Prognosis and management of acute myeloid leukemia in patients with Down syndrome. Issue 6 (December 2014) - Caldwell, J Timothy; Ge, Yubin; Taub, Jeffrey W
<x xml:space="preserve">Abstract</x> Children with Down syndrome (DS) are at a substantially increased risk to develop acute myeloid leukemia (AML). This increase in incidence is tempered, however, by favorable overall survival rates of approximately 80%, whereas survival for non-DS children with similar leukemic subtypes is <35%. In this review, the clinical studies that have contributed to this overall high survival will be presented and their individual successes will be discussed. Important issues including intensity of treatment regimens, the role of bone marrow transplants and prognostic indicators will be reviewed. In particular, the roles of high- vs low- vs very low-dose cytarabine will be discussed, as well as potential therapeutic options in the future and the direction of the field over the next 5 years. In summary, children with DS and AML should be treated with a moderate-intensity cytarabine-based regimen with curative intent.